(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article we can see the views of Abdurauf Fitrat, expressed in “The Story of an Indian Traveller,” on important aspects of social and political life of that time. Through this we will see the shortcomings of the society of the Emirat period and how it is critically expressed by the views of Fitrat. This work of Fitrat reveals the essence of Jadidism movement. Jadids aimed to change and fundamentally renew not only one area of life, but the whole life, the social system that oscillates it. This work analyzes the social and political significance of these goals.